Bears on wheels - Berenstain, Stan, 1923-2005.; Berenstain, Jan, 1923- (New York : Random House, 1969)
An acrobatic act begins with one bear on a unicycle and ends with twenty-one bears and sixteen wheels flying through the air.
Wilson's Children.
1.3
1.3
K-3.
K-3
Keywords: Counting; Bears -- Fiction; Counting